The Form of the Brahim Nalo Song in the Kalinong Musical Tradition in Kampung Baruh, Tabir District, Merangin Regency, Jambi Province - Bernanda Simatupang; Rosmegawaty Tindaon (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
This study aims to analyze the form and function of the song Brahim Nalo in the Kalinong musical tradition in Kampung Baruh, Tabir District, Merangin Regency, Jambi Province. The research employed a qualitative method with a descriptive-analytical approach through literature review, observation, interviews, and documentation. The findings reveal that Brahim Nalo has a simple compositional structure with short verses, a repeated answer melody performed twice, and no division between sections. Its musical form consists of a single complete melodic cycle with an interrogative phrase as the opening and a responsive phrase as the closing. Repetition functions as both a transition and reinforcement of the song’s message. In terms of function, Brahim Nalo serves as a medium of communication, emotional expression, entertainment, and aesthetic satisfaction, while also strengthening cultural identity, ensuring continuity of tradition, and fostering social cohesion among the people of Kampung Baruh. This study concludes that Brahim Nalo is not only of musical value but also plays a vital socio-cultural role, making it an integral part of community life and contributing to the preservation and enrichment of Indonesian traditional music.